Efektivitas Bimbingan Belajar Menghadapi Ujian Nasional Pelajaran Sosiologi SMA Muhammadiyah 2 Pontianak - Mariani, Vivi (UNIVERSITAS TANJUNGPURA, 2013)
The Research about The Effectiveness of Tutoring in the face of national examination in the subject of Sociology at SMA Muhammadiyah 2 Pontianak aims to determine the effectiveness of tutoring in the face of national exams in the subject of Sociology at SMA Muhammadiyah 2 Pontianak. The research used an expost facto method and form causal comparative research with a sample of 40 people. Statistical calculations indicate that there is a significant influence on the success of national examination tutoring, and contributions reached 70,2 %. It means there is concluded tutoring in national exams on the subject of sociology at SMA Muhammadiyah 2 Pontianak is effective.Key Words: Learning Guidance, National Exams Result.